Effects of nanoparticles loaded with Chaetomium globosum KMITL-NO805 extracts against leaf spot of rice Var. Sen Pidoa - Huyly Tann; Kasem Soytong (Malaysian Society of Applied Biology, 2016)
Nano-CGH, nano-CGE, and nano-CGM from Chaetomium globosum KMITL-N0805 expressed antifungal activity (ED50 values of 1.21, 1.19, and 1.93ppm/mL, respectively) against Curvularia lunata, the causal agent of leaf spot disease of rice var. Sen Pidoa. It was demonstrated that these nanoparticles caused the disruption and distortion of the pathogen cells, leading to their loss of pathogenicity. Tests in a pot experiment showed that nano-CGH, nano-CGE, and nano-CGM could significantly control leaf spot of rice var. Sen Pidoa. Based on the disease severity index at 60 days after treatment, nano-CGH and nano- CGM resulted in higher disease reduction (61.54%) than nano-CGE (53.83%). From these findings, it can be concluded that nano-CGH, nano-CGE, and nano-CGM have the ability to decrease leaf spot disease of rice var. Sen Pidoa caused by C.lunata. Moreover, the research showed that all three types of nanoparticles significantly increased the height and number of tillers of the rice plant relative to the non-treated control.